Assessment of the working conditions of the adjuster of molding and coremaking machines in foundries - A. M. Lazarenkov; I. A. Ivanov; M. A. Sadokha (Литьë и металлургия)
The results of the assessment of working conditions at the workplaces of the adjuster of molding and core making machines are presented, the factors of the production environment determining them are determined. The working conditions of the adjuster are considered in comparison with the standard values. It is established that when assessing the working conditions of a machine adjuster in the molding and core sections of foundries, it is necessary to take into account the equipment and hand tools used, and the length of time spent at the working equipment.